Relationship between Puberty and Inhibitory Control: Computational Modeling of the Drift-diffusion Process. Issue 5 (4th July 2021) - Castagna, Peter J.; Crowley, Michael J.
ABSTRACT: Previous work relies largely on the simple reaction time measures in inhibitory control tasks. The goal of the current study was to provide a better understanding the relationship between puberty, sex, and inhibitory control utilizing and contrasting two popular drift diffusion models. A sample of 103 adolescents ( M age  = 14.49, SD  = 1.69) self-reported their pubertal development and completed a flanker task. Utilizing Bayesian regressions, we found that the interaction between puberty and sex were significant predictors of the A/B parameter, conceptualized as the amount of information considered for a decision during the task.